Power Monitoring and Control with Integrated IoT for Housing Electrical System - Noorlan, Nik Nur Athirah Syamimi; Abu Hassan, Omar (Progress in Engineering Application and Technology, 2022)
Internet of Think (IoT) is becoming more popular for usage in the house, so the electrical load in the home can be regulated online using IoT devices that can be controlled from anywhere and at any time. Some of the causes of these changes include people's laziness or forgetfulness due to their hectic lifestyle. This initiative is being implemented to prevent this from happening, increasing power bills. People seek security in every situation, whether at home or away from home. This project system allows users to control the switching of electrical loads online through the phone, remotely control an electronic door lock, and receive notifications while interacting with the Blynk platform. Furthermore, this system is capable of controlling the use of current and power consumption in each residence. It is accessible online via the Blynk application[1]. This project's design system includes an Arduino as the primary function of the microcontroller to programmed the system, an ESP8266 as a Wi-Fi module, a 5v four relay channel, and a current sensor ACS712 and a PIR motion sensor. This programmed is based on the Internet of Things concept. The system has also been fully equipped with multiple sensors for control unit inputs, allowing users to control the switch in various ways, including online, via a sensor, or a manual button[2].